FREQUENCY OF USE OF NEOLOGISMS IN GOOGLE SERVICES IN UZBEKISTAN - Mukimova Hulkar Ibodulla qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This research investigates the usage patterns of popular neologisms by analyzing data collected from various Google services, including Google Trends and Google Ngram Viewer. The study focuses on identifying the frequency, regional distribution, and temporal dynamics of emerging lexical items commonly used in internet communication and social media. By examining search trends and textual occurrences, the research highlights how certain neologisms gain popularity and enter mainstream usage. The findings contribute to a better understanding of digital-era language evolution and the sociolinguistic factors influencing the adoption of new vocabulary.